2021
DOI: 10.1016/j.jid.2020.05.095
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B Contributes to Barrier Dysfunction in Oxazolone-Induced Skin Inflammation through E-Cadherin and FLG Cleavage

Abstract: Atopic dermatitis (AD) is the most common inflammatory skin condition. Skin barrier dysfunction is of major importance in AD because it facilitates allergen sensitization and systemic allergic responses. Long regarded as a pro-apoptotic protease, emerging studies indicate granzyme B (GzmB) to have extracellular roles involving the proteolytic cleavage of extracellular matrix, cell adhesion proteins, and basement membrane proteins. Minimally expressed in normal skin, GzmB is elevated in AD and is positively cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 55 publications
0
49
0
Order By: Relevance
“…108 Turner et al confirmed that GZMB impaired the epithelial barrier function through Ecadherin and filaggrin cleavage, and VTI-1002 reduced the severity of skin barrier dysfunction in atopic dermatitis (the most commonly occurring inflammatory skin condition). 94 These studies suggest the therapeutic potential of VTI-1002 for GZMB-induced/aggravated diseases. PI-9 is an endogenous GZMB inhibitor that can bind to GZMB in the cytosol of activated CD8 + T cells.…”
Section: Inhibitorsmentioning
confidence: 89%
See 2 more Smart Citations
“…108 Turner et al confirmed that GZMB impaired the epithelial barrier function through Ecadherin and filaggrin cleavage, and VTI-1002 reduced the severity of skin barrier dysfunction in atopic dermatitis (the most commonly occurring inflammatory skin condition). 94 These studies suggest the therapeutic potential of VTI-1002 for GZMB-induced/aggravated diseases. PI-9 is an endogenous GZMB inhibitor that can bind to GZMB in the cytosol of activated CD8 + T cells.…”
Section: Inhibitorsmentioning
confidence: 89%
“…16 Turner et al have confirmed that GZMB contributes to barrier dysfunction in oxazoloneinduced skin inflammation through E-cadherin and filaggrin cleavage. 94 GZMB also induces the cleavage of membraneassociated guanylate kinases (MAGUKs); MAGUKs constitute a family of proteins that are typically associated with cell junctions and play a major role in the organization of proteinprotein complexes in plasma membranes. GZMB-mediated cleavage of MAGUKs (including membrane-associated guanylate kinase with inverted orientation protein (MAGI)-1, MAGI-2, MAGI-3, disc large homolog 1, post-synaptic density (PSD)-95, PSD-93, synapse-associated protein 102, zonula occludens (ZO)-1 and ZO-3) in vitro demonstrates its importance in the rapid and proper disruption of cell-cell contacts and in the isolation of a dying cell during apoptosis.…”
Section: Gzmb and Elimination Of Viruses Or Virus-infected Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, granzymes A and B contributed to LPS-induced cell shedding in a perforin-independent manner, providing strong evidence that gd IELs facilitate cell shedding through a mechanism other than direct lysis. Extracellular granzyme has been shown to promote the proteolytic cleavage of ECM proteins such as laminin, type IV collagen, and fibronectin, which are found in the intestinal BM [53][54][55][56][57][58][59] . This has been shown to contribute to cell death, as GzmB-mediated matrix remodeling can induce the detachment and apoptosis of cultured endothelial and transformed epithelial cells 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the cause of the itch was complicated, there were still some common factors that existed. Multiple immune cells participate in pruritus of the irritated itch model mice, including mast cells and CD4 + and CD8 + T lymphocytes (31,32). Like keratinocytes, mast cells are a major source of cutaneous proinflammatory mediators thought to underlie the pathology of pruritus, most importantly IL-33, IL-4, and IL-13 (29,33,34).…”
Section: Introductionmentioning
confidence: 99%